Intelligent systems for security informatics - Yang, Christopher C. (Intelligent systems series., 2013)
The Intelligent Systems Series comprises titles that present state-of-the-art knowledge and the latest advances in intelligent systems. Its scope includes theoretical studies, design methods, and real-world implementations and applications. The most prevalent topics in Intelligence and Security Informatics (ISI) include data management, data and text mining for ISI applications, terrorism informatics, deception and intent detection, terrorist and criminal social network analysis, public health and bio-security, crime analysis, cyber-infrastructure protection, transportation infrastructure security, policy studies and evaluation, and information assurance, among others. This book covers the most active research work in recent years. Pulls together key information on ensuring national security around the worldThe latest research on this subject is concisely presented within the book, with several figures to support the text. Will be of interest to attendees of The Intelligence and Security Informatics conference series, which include IEEE International Conference on Intelligence and Security Informatics (IEEE ISI).